1982
DOI: 10.1111/j.1471-4159.1982.tb08657.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Neuronal‐Glial Metabolism of Glutamate by the Neurotoxin Kainic Acid

Abstract: The effect of the excitotoxin kainic acid on glutamate and glutamine metabolism was studied in cerebellar slices incubated with D-[2-14C]glucose, [U-14C]gamma-aminobutyric acid, [3H]acetate, [U-14C]glutamate, and [U-14C]glutamine as precursors. Kainic acid (1 mM) strongly inhibited the labeling of glutamine relative to that of glutamate from all precursors except [2-14C]glucose and [U-14C]glutamine. Kainic acid did not inhibit glutamine synthetase directly. The data indicate that in the cerebellum kainic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
38
2

Year Published

1983
1983
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 43 publications
8
38
2
Order By: Relevance
“…A decrease of extracellular glutamine during the increase of glutamate is frequently observed in response to CNS challenges (Krespan et al, 1982;Lehman et al, 1983). This inverse change may reflect the compartmentation of glutamate-glutamine metabolism in the brain and the precursor role of glutamine for neurotransmitter glutamate (Ottersen et al, 1992;Huang et al, 1994;Westergaard et al, 1995;McKenna et al, 1996;Zielke et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…A decrease of extracellular glutamine during the increase of glutamate is frequently observed in response to CNS challenges (Krespan et al, 1982;Lehman et al, 1983). This inverse change may reflect the compartmentation of glutamate-glutamine metabolism in the brain and the precursor role of glutamine for neurotransmitter glutamate (Ottersen et al, 1992;Huang et al, 1994;Westergaard et al, 1995;McKenna et al, 1996;Zielke et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…In several tissues, KA causes a net release of endogenous Glu and aspartate (Asp; Ferkany et al, 1982;Krespan et al, 1982;Ferkany and Coyle, 1983a,b;Pastuszko et al, 1984;Poli et al, 1985). In some cases, KA may enhance synaptic release of EAAs by stimulating presynaptic receptors (Cox and Bradford, 1978;Ferkany et al, 1982;Krespan et al, 1982;Collins et al, 1983;Coyle, 1983;Ferkany and Coyle, 1983a;Pastuszko et al, 1984;Young et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In several tissues, KA causes a net release of endogenous Glu and aspartate (Asp; Ferkany et al, 1982;Krespan et al, 1982;Ferkany and Coyle, 1983a,b;Pastuszko et al, 1984;Poli et al, 1985). In some cases, KA may enhance synaptic release of EAAs by stimulating presynaptic receptors (Cox and Bradford, 1978;Ferkany et al, 1982;Krespan et al, 1982;Collins et al, 1983;Coyle, 1983;Ferkany and Coyle, 1983a;Pastuszko et al, 1984;Young et al, 1988). However, there is also evidence that KAinduced blockade of Glu/Asp uptake can be a primary event in producing an increase in extracellular Glu and Asp (Lakshamanan et al, 1974;McGeer et al, 1978;Johnston et al, 1979;Krespan and Padmanaban, 1982;Pastuszko et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still much debate as to whether it does this by enhancing transmitter glutamate release via a Ca2+dependent (neuronally-derived) or Ca2 +-independent (probably derived from both neuronal and nonneuronal elements) mechanism, or whether the increase in the extracellular concentration of glutamate is mediated merely through the ability of KA to inhibit the high affinity neuronal and/or glial uptake of glutamate (Johnston et al, 1979). In contrast, however, other in vitro release studies suggested that KA increases synaptic glutamate concentrations by a calcium-independent release mechanism involving non-neuronal elements (Nicklas et al, 1980;Krespan et al, 1982) possibly coupled with inhibition of the high affinity (neuronal and/or glial) uptake process (Notman et al, 1984). This is wholly consistent with a major part of the action of KA being on synaptic transmitter pools of glutamate.…”
Section: Discussionmentioning
confidence: 99%